(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Human Resources Outsourcing (HRO) has emerged as a strategic practice within the realm of business, allowing organizations to delegate HR functions to specialized service providers. The effectiveness of HRO engagements hinges upon the caliber of the rapport established between the outsourcing entities and the service providers. This research delves into the "Impact of Relationship Quality on the Success of Human Resources Outsourcing - From the Lens of Service Providers." Employing a blend of qualitative and quantitative methodologies, data were garnered from (WEDO HR), a service provider offering HR outsourcing services. The study uncovers that the quality of the relationship holds a pivotal role in determining the triumph of HRO undertakings, as perceived by service providers. Forging a robust and collaborative partnership between service providers and outsourcing organizations exerts significant influence over the overarching outcomes of HRO projects. Key determinants of success identified by service providers encompass elements such as trust, effective communication, shared understanding, unwavering commitment, and skillful conflict resolution. Furthermore, the establishment of an efficient partnership streamlines HR processes, elevates the caliber of service delivery, and facilitates the seamless transfer of knowledge, yielding benefits for both parties involved. The study concludes by offering a spectrum of recommendations and best practices aimed at heightening the quality of relationships within HRO engagements. Service providers are encouraged to channel efforts into cultivating relationships, nurturing trust, and taking a proactive stance in resolving conflicts to ensure enduring success. On the other hand, outsourcing organizations can enhance collaboration by establishing transparent communication channels, formulating pragmatic expectations, and acknowledging the intrinsic value of relationship quality in realizing shared objectives. To encapsulate, this research casts a spotlight on the pivotal role that relationship quality plays in the triumph of HRO, particularly through the perspective of service providers. The insights gleaned from this study furnish valuable guidance for outsourcing organizations, service providers, and practitioners striving to optimize HRO outcomes and foster enduring partnerships in the ever-evolving landscape of HR outsourcing